The Interaction of Different Phospholipids on the Blood Clotting Mechanism - Bourgain, R. H; Kahn, M. J. P (Thrombosis and Haemostasis, 1967)
The interaction of cephalin and a phosphoinositide fraction extracted from beef brain was investigated. Variance analysis performed on the experimental data evidence a highly significant interaction between the 2 moieties as could be observed graphically by the non-parallelism of the regression lines.